Overload of the fourth age Family caregiver of the elderly (Research, Society and Development, 2020)
Objective: to analyze scientific evidence available in the health literature, in relation to the burden of elderly family caregivers in the elderly. Method: descriptive-discursive study of an integrative review conducted in January and February 2020, based on data: National Library of Medicine, Latin American and Caribbean Literature in Health Sciences and on-line library of the Scientific Electronic Library. Results: caregivers are mostly family members, women, daughters, residents of the same Long-Term Institution and responsible for daily care, and with limited capacities. Show that among the factors that negatively affect the quality of life of caregivers, include the degree of dependence of the elderly and the stress on the caregiver. Conclusion: the theme of quality of life for elderly family caregivers is still little explored in the literature, especially with regard to the elderly. It is suggested that further studies be conducted with a more general approach, regardless of the elderly's disease, since the need for caregivers is indispensable for the elderly with physical and / or cognitive disabilities, and the greater the number of tasks in caring for the elderly , the greater the burden on the caregiver and, consequently, will affect their quality of life.